It depends what you consider as an analytical solution. If you consider a Fourier series as an analytical solution, you have this:
$$i \hbar \frac{\partial \Psi (\mathbf{r},t)}{\partial t} = -\frac{\hbar^{2}}{2m} \nabla^{2} \Psi(\mathbf{r},t)$$
Let's say you can use separation of variables and assume this for your wave function as:
$$\Psi(\mathbf{r},t) = F(\mathbf{r}) T(t)$$
So:
$$i \hbar F T^{'} = -\frac{\hbar^{2}}{2m} T \nabla^{2} F$$
or:
$$i \frac{2 m}{\hbar} \frac{T^{'}}{T} = -\frac{1}{F} \nabla^{2} F = \lambda^{2}$$
You have this for temporal part:
$$T(t) = \exp(-i \frac{\hbar}{2m} \lambda^{2} t)$$
For spatial part:
$$\nabla^{2}F + \lambda^{2} F = 0$$
The spatial part equation is just a Helmholtz equation. Now, it depends what geometry you have here. If it is just a cube in three-dimensional space:
$$F(\mathbf{r}) = X(x)Y(y)Z(z)$$
You have:
$$X^{''}YZ + XY^{''}Z + XYZ^{''} + \lambda^{2} XYZ = 0$$
or:
$$\frac{X^{''}}{X} + \frac{Y^{''}}{Y} + \frac{Z^{''}}{Z} + \lambda^{2} = 0$$
or:
$$\frac{X^{''}}{X} = - \frac{Y^{''}}{Y} - \frac{Z^{''}}{Z} - \lambda^{2} = -k_{x}^{2}$$
So:
$$X^{''} + k_{x}^{2} X = 0$$
$$Y^{''} + k_{y}^{2} Y = 0$$
$$Z^{''} + k_{z}^{2} Z = 0$$
and:
$$k_{x}^{2} + k_{y}^{2} + k_{z}^{2} = \lambda^{2}$$
$$X(x) = A_{x} \cos{(k_{x}x)} + B_{x} \sin{(k_{x}x)}$$
$$Y(y) = A_{y} \cos{(k_{y}y)} + B_{y} \sin{(k_{y}y)}$$
$$Z(z) = A_{z} \cos{(k_{z}z)} + B_{z} \sin{(k_{z}z)}$$
If you have Dirichlet boundary condition of zero at all boundaries of cube, you have:
$$X(x) = B_{x} \sin{(\frac{n\pi}{L_{x}}x)}$$
$$Y(y) = B_{y} \sin{(\frac{m\pi}{L_{y}}y)}$$
$$Z(z) = B_{z} \sin{(\frac{l\pi}{L_{z}}z)}$$
Where $L_{x}$, $L_{y}$, and $L_{z}$ are the length of the cube, $n$, $m$, and $l$ are integers, so:
$$k_{x} = \frac{n \pi}{L_{x}}$$
$$k_{y} = \frac{m \pi}{L_{y}}$$
$$k_{z} = \frac{l \pi}{L_{z}}$$
$$\lambda^{2}_{n,m,l} = \Bigg(\frac{n \pi}{L_{x}}\Bigg)^{2} + \Bigg(\frac{m \pi}{L_{y}}\Bigg)^{2} + \Bigg(\frac{l \pi}{L_{z}}\Bigg)^{2}$$
Finally:
$$\Psi_{n,m,l}(x,y,z,t) = B_{n,m,l} \sin{(\frac{n\pi}{L_{x}}x)} \sin{(\frac{m\pi}{L_{y}}y)} \sin{(\frac{l\pi}{L_{z}}z)} \exp(-i \frac{\hbar}{2m} \lambda^{2}_{n,m,l} t)$$
and
$$\Psi(x,y,z,t) = \sum_{n}\sum_{m}\sum_{l} B_{n,m,l} \sin{(\frac{n\pi}{L_{x}}x)} \sin{(\frac{m\pi}{L_{y}}y)} \sin{(\frac{l\pi}{L_{z}}z)} \exp(-i \frac{\hbar}{2m} \lambda^{2}_{n,m,l} t)$$
If for initial condition: $$\Psi(x,y,z,0) = \Psi_{0}(x,y,z)$$
$$B_{n,m,l} = \frac{1}{L_{x}L_{y}L_{z}}\int_{0}^{L_{x}} \int_{0}^{L_{y}} \int_{0}^{L_{z}} \Psi_{0}(x,y,z) \sin{(\frac{n\pi}{L_{x}}x)} \sin{(\frac{m\pi}{L_{y}}y)} \sin{(\frac{l\pi}{L_{z}}z)} dx dy dz$$
Note that the frequency of your system is defined as:
$$\omega = \frac{\hbar}{2m} \mathbf{k} \cdot \mathbf{k}$$
Where:
$$\mathbf{k} = (k_{x},k_{y},k_{z})$$
The energy of the system is defined as:
$$E = \hbar \omega = \frac{\hbar^{2}}{2m} \mathbf{k} \cdot \mathbf{k}$$
So rewriting the solution:
$$\Psi(x,y,z,t) = \sum_{n}\sum_{m}\sum_{l} B_{n,m,l} \sin{(\frac{n\pi}{L_{x}}x)} \sin{(\frac{m\pi}{L_{y}}y)} \sin{(\frac{l\pi}{L_{z}}z)} \exp(-i\omega_{n,m,l} t)$$
Where:
$$\omega_{n,m,l} = \frac{\hbar}{2m} \Bigg( \Big ( \frac{n \pi}{L_{x}} \Big )^{2} + \Big ( \frac{m \pi}{L_{y}} \Big )^{2} + \Big ( \frac{l \pi}{L_{z}} \Big )^{2} \Bigg)$$
So, now you have an analytical solution by means of Fourier series to examine the error and convergence rate your numerical implementation.
Update: For an initial Gaussian wave packet of the form:
$$\Psi(x,y,z,0) = \Psi_{0}(x,y,z) = \sqrt[\leftroot{-2}\uproot{2}4]{\frac{1}{\sigma_{0}^{2} \pi}} \exp{(i \mathbf{k} \cdot \mathbf{r} - \frac{|\mathbf{r} - \mathbf{r}_{0}|^{2}}{2 \sigma_{0}^{2}})}$$
Where: $\mathbf{k} = (k_{x}, k_{y}, k_{z})$, $\mathbf{r} = (x, y, z)$, $\mathbf{r}_{0} = (\frac{L_{x}}{2}, \frac{L_{y}}{2}, \frac{L_{z}}{2})$.
So:
$$B_{n,m,l} = \frac{1}{L_{x}L_{y}L_{z}}\int_{0}^{L_{x}} \int_{0}^{L_{y}} \int_{0}^{L_{z}} \Psi_{0}(x,y,z) \sin{(\frac{n\pi}{L_{x}}x)} \sin{(\frac{m\pi}{L_{y}}y)} \sin{(\frac{l\pi}{L_{z}}z)} dx dy dz$$
But this 3D integral could be broken down to three 1D integrals of:
$$\mathcal{I}_{x} = \frac{1}{L_{x}} \int_{0}^{L_{x}} \exp{(i k_{x}x - \frac{(x - \frac{L_{x}}{2})^{2}}{2 \sigma_{0}^{2}})} \sin{(k_{x} x)} dx$$
$$\mathcal{I}_{y} = \frac{1}{L_{y}} \int_{0}^{L_{y}} \exp{(i k_{y}y - \frac{(y - \frac{L_{y}}{2})^{2}}{2 \sigma_{0}^{2}})} \sin{(k_{y} y)} dy$$
$$\mathcal{I}_{z} = \frac{1}{L_{z}} \int_{0}^{L_{z}} \exp{(i k_{z}z - \frac{(z - \frac{L_{z}}{2})^{2}}{2 \sigma_{0}^{2}})} \sin{(k_{z} z)} dz$$
But:
$$\mathcal{I}_{x} = i\frac{\sigma_{0}}{2L_{x}} \sqrt{\frac{\pi}{2}} (2 \mathrm{erf} (\frac{L_{x}}{2 \sqrt{2} \sigma_{0}}) + \exp{(-2 \sigma_{0}^{2} k_{x}^{2} + i k_{x} L_{x})} (\mathrm{erf} (\frac{- \frac{L_{x}}{2} + i 2 \sigma_{0}^{2} k_{x}}{\sqrt{2} \sigma_{0}}) - \mathrm{erf} (\frac{\frac{L_{x}}{2} + i 2 \sigma_{0}^{2} k_{x}}{\sqrt{2} \sigma_{0}})))$$
$$\mathcal{I}_{y} = i\frac{\sigma_{0}}{2L_{y}} \sqrt{\frac{\pi}{2}} (2 \mathrm{erf} (\frac{L_{y}}{2 \sqrt{2} \sigma_{0}}) + \exp{(-2 \sigma_{0}^{2} k_{y}^{2} + i k_{y} L_{y})} (\mathrm{erf} (\frac{- \frac{L_{y}}{2} + i 2 \sigma_{0}^{2} k_{y}}{\sqrt{2} \sigma_{0}}) - \mathrm{erf} (\frac{\frac{L_{y}}{2} + i 2 \sigma_{0}^{2} k_{y}}{\sqrt{2} \sigma_{0}})))$$
$$\mathcal{I}_{z} = i\frac{\sigma_{0}}{2L_{z}} \sqrt{\frac{\pi}{2}} (2 \mathrm{erf} (\frac{L_{z}}{2 \sqrt{2} \sigma_{0}}) + \exp{(-2 \sigma_{0}^{2} k_{z}^{2} + i k_{z} L_{z})} (\mathrm{erf} (\frac{- \frac{L_{z}}{2} + i 2 \sigma_{0}^{2} k_{z}}{\sqrt{2} \sigma_{0}}) - \mathrm{erf} (\frac{\frac{L_{z}}{2} + i 2 \sigma_{0}^{2} k_{z}}{\sqrt{2} \sigma_{0}})))$$
So:
$$B(k_{x},k_{y},k_{z}) = \sqrt[\leftroot{-2}\uproot{2}4]{\frac{1}{\sigma_{0}^{2} \pi}} \mathcal{I}_{x} \mathcal{I}_{y} \mathcal{I}_{z}$$